Recent Achievements in Photoelectrocatalytic Degradation of Pesticides - Salazar-Gonzalez, R; Sandoval, A; Sandoval, A (Elsevier B.V., 2022)
This review summarizes recent advances in photoelectrocatalysis of pesticides, involving fundamentals, the preparation of photoanodes, and their application in the degradation of pesticides from distinct types of water. The effect of the chemical nature of the photoanodes to enhance the electrolysis and photolysis processes is discussed in this work. The use of different semiconductors for the degradation of pesticides was also described under different experimental conditions, all of them still at the laboratory level and under synthetic experimental conditions, which serve as the basis for real application in the short term. Outlooks and perspectives are provided and discussed. © 2022 Elsevier B.V.